Binding energies of tyrosine kinase inhibitors: Error assessment of computational methods for imatinib and nilotinib binding. (October 2015) - Fong, Clifford W.
Graphical abstract: Highlights: Tyrosine kinase inhibitors. Quantum mechanics. Binding energies. Error assessment. Abstract: The binding energies of imatinib and nilotinib to tyrosine kinase have been determined by quantum mechanical (QM) computations, and compared with literature binding energy studies using molecular mechanics (MM). The potential errors in the computational methods include these critical factors: Errors in X-ray structures such as structural distortions and steric clashes give unrealistically high van der Waals energies, and erroneous binding energies. MM optimization gives a very different configuration to the QM optimization for nilotinib, whereas the imatinib ion gives similar configurations Solvation energies are a major component of the overall binding energy. The QM based solvent model (PCM/SMD) gives different values from those used in the implicit PBSA solvent MM models. A major error in inhibitor—kinase binding lies in the non-polar solvation terms. Solvent transfer free energies and the required empirical solvent accessible surface area factors for nilotinib and imatinib ion to give the transfer free energies have been reverse calculated. These values differ from those used in the MM PBSA studies. An intertwined desolvation—conformational binding selectivity process is a balance of thermodynamic desolvation and intramolecular conformational kinetic control. The configurational entropies ( T Δ S ) are minor error sources.